Practicality and Effectiveness of Chemical Ludo Games as Learning Media of Acid and Base Materials to Students of Class XI SMA/MA - Iswendi, Iswendi; Husni, Hikmah Ibnu (FKIP - Universitas Riau, 2023)
This research is a continuation of the development research conducted by Rentia Lestari with a valid 4-D model but has not been tested for its practicality and effectiveness. The study aims to determine the level of practicality and level of effectiveness of chemical ludo games as a medium of learning of acid and base materials against student learning outcomes. The study was designed by Pretest-Posttest Control Group Design. The research objects are Class XI Mipa 1 (control class) and Class XI Mipa 2 (experiment class) at SMA N 1 V Koto Kampung Dalam. Pre-testing and posttesting. The practicality data was analyzed with the percentage of practicality and effectiveness with N-Gain. Data analysis results are practical in teachers at a very practical level and students are at a fairly practical, for the effectiveness of the data analysis results show quite effective, which is supported by an improved understanding of the learning outcomes of the higher experimental class compared to the control class. The average post-test scores of the experimental and control classes of 77.14 and 70.15 respectively and the analysis results with the N-Gain experimental class of 0.59 were at a fairly effective rate and the control class of 0.51 was at a less effective rate, the learning results of the experimental class increased than the control Class where tcount (3.62) > ttable(1.67) at the real level α= 0.05. This indicates increased learning outcomes.